USAHA KANTOR URUSAN AGAMA DALAM PENYELESAIAN BUKU NIKAH HILANG DI KANTOR URUSAN AGAMA KECAMATAN NGAWEN, GUNUNGKIDUL TAHUN 2024 - Amin, Muhammad; Baehaqi, B; Abdullah, Mu'in (AL HUKMU: Journal of Islamic Law and Economics, 2025)
The main problem faced in this study is related to the importance of maintaining a marriage book for brides who have been legally married in religion and the State. With unexpected possibilities such as lost, damaged or ineligible marriage books, efforts are needed to issue duplicate marriage books published by the KUA of the ngawen sub-district of Gunungkidul Regency to people in need. In this study the authors used descriptive qualitative methods and a naturalistic phenomenological approach. Then, in collecting data in this study using observation in the research area, interviews with research subjects and informants, and also documentation in every research activity. The analysis of the research used is a field study technique on research subjects and research informants from the community and KUA employees of Ngawen sub- district, Gunungkidul. And to check the truth of the research data and the degree of trust in it, this research is carried out through capability, transferability, and objectivity. The results of this study indicate that the marriage book is very important and valuable for its owner after carrying out a legal marriage recognized by religion and the State. So that in the future it can be used for civil interests if needed, as well as showing the ease of managing the issuance of duplicate marriage books at the Religious Affairs Office of the Ngawen sub-district, Gunungkidul.